2013
DOI: 10.1038/onc.2013.403
|View full text |Cite
|
Sign up to set email alerts
|

HRG-1 enhances cancer cell invasive potential and couples glucose metabolism to cytosolic/extracellular pH gradient regulation by the vacuolar-H+ ATPase

Abstract: Haeme-responsive gene (HRG)-1 encodes a 16-kDa transmembrane protein that is induced by insulin-like growth factor-1 (IGF-1) and associates with the vacuolar-(H(+)) ATPase (V-ATPase). We previously reported that HRG-1 is essential for V-ATPase activity in endosomal acidification and receptor trafficking. Here, we show that in highly invasive and migratory cancer cell lines, HRG-1 and the V-ATPase are co-expressed at the plasma membrane, whereas in less invasive cell lines and non-transformed cells HRG-1 over-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…This is termed the Warburg effect and is associated with tumor hypoxia as well as activation of oncogenes, such as MYC and RAS, and inactivation of tumor suppressors, such as p53 65, 66, 67. This results in production of lactic acid and H + , and plasma membrane V‐ATPase may be key under these conditions for maintaining intracellular pH homeostasis 68. In addition, via its action as a coordinator of regulators of opposing anabolic versus catabolic pathways (eg, mediated via mTORC1 or AMPK, respectively) 10.…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…This is termed the Warburg effect and is associated with tumor hypoxia as well as activation of oncogenes, such as MYC and RAS, and inactivation of tumor suppressors, such as p53 65, 66, 67. This results in production of lactic acid and H + , and plasma membrane V‐ATPase may be key under these conditions for maintaining intracellular pH homeostasis 68. In addition, via its action as a coordinator of regulators of opposing anabolic versus catabolic pathways (eg, mediated via mTORC1 or AMPK, respectively) 10.…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…Moreover, V-ATPase mutations that impair binding to phosphofructokinase-1 are associated with distal renal tubular acidosis (24), and V-ATPase regulation by glycolysis plays a role in viral infections (40) and the metabolic switch in cancers (41,42). It has been proposed that glycolytic enzymes form a supercomplex with V-ATPase that funnels ATP directly to VATPase and propels proton transport (21,24,32,34,37,43).…”
Section: Connecting Glucose Metabolism To V-atpase Assemblymentioning
confidence: 99%
“…[10][11][12][13] Recently, it has been shown that the expression of this proton pump is upregulated in several cancers, including colon cancer, even though its role in the latter remains poorly characterized. [14][15][16][17] TM9SF4 is a transmembrane protein belonging to the transmembrane-9 superfamily (TM9SF), which is a well-defined family of proteins characterized by a large hydrophilic N-terminal domain followed by nine transmembrane domains. 18 Although little is known about their function, these proteins have been implicated in adhesion, phagocytosis and innate immunity.…”
Section: Introductionmentioning
confidence: 99%